Prognosis-related genes participate in immunotherapy of renal clear cell carcinoma possibly by targeting dendritic cells - Fang, Guodong; Wang, Xudan (Frontiers in Cell and Developmental Biology, 2022)
Tumour immunotherapy has become one of the most promising approaches to tumour treatment. This study aimed to screen genes involved in the response of clear cell renal cell carcinoma (ccRCC) to immunotherapy and analyse their function. Based on the Gene Expression Omnibus and The Cancer Genome Atlas (TCGA) datasets, we screened out nine differentially expressed genes (TYROBP, APOC1, CSTA, LY96, LAPTM5, CD300A, ALOX5, C1QA, and C1QB) associated with clinical traits and prognosis. A risk signature constructed by the 9 genes could predict the survival probability for patients at 1 year, 3 years, and 5 years. The immune checkpoint blockade response rate in the high-risk group was significantly higher than in the low-risk group (49.25% vs. 24.72%, p≤0.001). The 9 prognosis-related genes were negatively correlated with activated dendritic cells in the low-risk group but not in the high-risk group. qRT‒PCR, immunohistochemistry and immunofluorescence showed that the 9 prognosis-related genes were associated with dendritic cell activity and the PD-1 positive staining rate. In conclusion, the 9 prognosis-related genes have high prognostic value. The patients in the high-risk group were more likely to benefit from immunotherapy, and the mechanism might be related to the release of dendritic cells-mediated immunosuppression.